Training New Housing Entrepreneurs — A Malaysian Scenario - Jaafar, Mastura; Syed Abu Bakar, Syed Putra; Wan Daud, Wan Mohd Dzulkifli (Intech, 2015)
Housing is a basic human need that not only serves as a shelter, but also is a simultaneous source of luxury, investment, privacy, and comfort. In Malaysia, the housing sector is an indispensable indicator of economic empowerment because the meeting of housing needs for all people has long been an objective of national policy [1]. Housing is an important wealth constituent [2] that affects the welfare of all people either directly or indirectly [3] in the form of improved living environments. Moreover, the housing sector significantly affects the macroeconomy of Malaysia: in 1996, it contributed 4.5% to the growth domestic product [4] and acted as a tool to ‘pump prime’ the economy following the Asian financial crisis from 1997 to 1998 [5].